2016
DOI: 10.1093/jamia/ocw010
|View full text |Cite
|
Sign up to set email alerts
|

Applying probabilistic temporal and multisite data quality control methods to a public health mortality registry in Spain: a systematic approach to quality control of repositories

Abstract: Multisite and temporal variability in data distributions affects DQ, hindering data reuse, and an assessment of such variability should be a part of systematic DQ procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 36 publications
0
40
0
3
Order By: Relevance
“…Work on identifying issues in sharing data between sites was another trend this year. Saez et al [9], discussed the issue of data quality, but other issues addressed include the difficulty in understanding what's in a large data collection, and issues in maintaining patient privacy when datasets are shared publically. Demner-Fushman's paper on preparing radiology examination documents for distribution, including de-identification and indexing, noted that "an important step in facilitating secondary use of clinical document collections is easy access to descriptions and samples that represent the content of the collections" [10].…”
Section: Discussionmentioning
confidence: 99%
“…Work on identifying issues in sharing data between sites was another trend this year. Saez et al [9], discussed the issue of data quality, but other issues addressed include the difficulty in understanding what's in a large data collection, and issues in maintaining patient privacy when datasets are shared publically. Demner-Fushman's paper on preparing radiology examination documents for distribution, including de-identification and indexing, noted that "an important step in facilitating secondary use of clinical document collections is easy access to descriptions and samples that represent the content of the collections" [10].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we input missing data using the nearest neighbors (NN) algorithm. Secondly, we assessed the multisource variability . According to the results, we subgrouped the variables of migraine intensity and migraine frequency in order to ensure intergroup differences.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, they observed that "a process that standardizes the laboratory results in the CDW will necessitate frequent updates to stay current." The notion of temporal quality was explored by Sáez et al [18] on a Spanish public health mortality registry using methods based on information theory and geometry.…”
Section: Related Workmentioning
confidence: 99%